Applied innovation: Technological experiments on biomimetic façade systems and solar panels - Livio Petriccione; Fabio Fulchir; Francesco Chinellato (Techne, 2021)
The most advanced technological concepts aim to obtain an “organic” behaviour of the building envelope, which consequently becomes “dynamic” and variable because it is sensitive and self-adapting with respect to external environmental conditions. In this highly innovative context, solar shielding devices become important and, in some cases, they can be integrated with special types of glasses or with “active” components, such as solar panels. Instead, the orientation systems of solar devices, described below, use only the thermal expansion to self-regulate, combining the reduction of energy consumption with minimum environmental impact, without the aid of motors, computerised devices or external energy sources, overcoming some critical issues of the self-adaptive envelopes used to date.